Mengenal Kecerdasan Buatan : Edukasi Artificial Intelligence untuk Siswa SMP di Desa Sinar Bhakti - M Mahfudz Siddiq; Karel Kholis Aditya; Angga Pratama; Resko Ardiyansyah; Umi Sahara (Universitas Maritim AMNI Semarang, 2025)
Technological advancements emphasize the importance of artificial intelligence (AI) literacy for younger generations. However, junior high school students in Sinar Bhakti Village still lack basic knowledge of AI. This community service program aims to introduce the fundamental concepts of AI to junior high school students through an interactive educational approach. The method employed involved practice-based workshops using visual media and simple simulations. The activity was met with high enthusiasm from the students, especially during simulations related to the application of AI in daily life. The results showed an improvement in students' understanding of AI concepts, as reflected in their ability to articulate the materials taught during the program. Furthermore, this program provided students with new insights into the potential of future technologies and created an active space for discussions on AI applications in various fields.